Dynamics of The Labor System (Kafala) in Qatar - Wawan Wawan; Muhammad Sya'roni Rofii (Universitas Muhammadiyah Gorontalo, 2022)
Although the kafala system remains in place in most GCC countries, Qatar has undertaken significant reforms and ratified a number of conventions related to human rights, such as those on the prevention of human trafficking and the protection of children. The purpose of this study is to describe the labor system (Kafala) that has long been adopted by GCC countries, including Qatar. Qatar is the only country that is progressive enough to reform its migrant worker policy. This research is qualitative because the instrument used is a document study. The results of this study indicate that the number of high dependence on migrant workers is quite high and vulnerable to labor scandals. This is further exacerbated by the mobilization of migrant workers to welcome the grand event of the four years, the 2022 World Cup. The phenomenon is growing massively, including reports from the International Human Rights Institute, Amnesty International and the International Labor Organization (ILO) forcing the Qatari government to make adjustments